Characterising longitudinal alterations in postural control following lower limb injury in professional rugby union players - McCarthy-Ryan, M. F.; Mellalieu, S.; Bruton, A.; Moore, I. (ISBS Proceedings Archive (Michigan), 2022)
Assessment of player`s postural control following a lower limb injury is of interest to sports science and medicine practitioners due to its fundamental role in daily tasks and sporting activities. The purpose of this study was to measure the longitudinal changes in rugby union player`s postural control throughout return to play (RTP) following lower limb injury. Rehabilitation was divided into three phases - acute, middle and late. Nine players from a professional rugby union team (height 1.80±0.06 m; mass 96.1±13.2 kg; age 25±3 years) were included in this study. Static unilateral postural control was measured in the acute phase using a PASCO dual axis force platform (PS-2142). Dynamic postural control was measured using single axis PASCO force platforms (PS-2141) with the middle phase being assessed by unilateral drop jump and the late phase a unilateral lateral hurdle hop. During the acute phase, no improvement were observed between the initial testing session and end testing session, nor any differences between the end of the acute rehabilitation phase and pre-injury baseline. Whereas for the middle and late phase improvements were observed between the initial and end testing session, with smaller magnitudes of dynamic postural control adjustment (DPCA; p <0,05). However, when comparing the end testing session of the middle and late phase of RTP to pre-injury baseline deficits were reported in the ability to restore postural control to pre-injury levels, with larger magnitudes of DPCA (p <0.05). Therefore, greater focus in players` RTP programmes needs to be given to the dynamic postural control players have on landing.